Diets rich in eicosapentaenoic acid and γ-linolenic acid affect phospholipid fatty acid composition and production of prostaglandins E1, E2 and E3 in turbot (Scophthalmus maximus), a species deficient in Δ5 fatty acid desaturase - Bell, J Gordon; Tocher, Douglas R; MacDonald, Fiona M; Sargent, John R (Prostaglandins, Leukotrienes and Essential Fatty Acids, 1995)
Duplicate groups of juvenile turbot, (Scophthalmus maximus), were fed diets containing either Marinol K (MO), a marine fish oil rich in eicosapentaenoic acid (EPA; 20:5, n-3) or borage oil (BO), rich in γ-linolenic acid (GLA; 18:3, n-6), for a period of 12 weeks. Individual phospholipid fatty acid compositions from hearts of fish fed BO had significantly more 18:2, n-6, GLA, 20:2, n-6, dihomo-γ-linolenic acid (DHGLA; 20:3, n-6) and total n-6 polyunsaturated fatty acids (PUFA), but significantly less arachidonic acid (AA; 20:4, n-6), compared to fish fed MO. In both phosphatidylcholine (PC) and phosphatidylethanolamine (PE) from heart, the DHGLA was increased by over 50-fold in fish fed BO while AA was reduced by over two-thirds, compared to fish fed MO. In brain, EPA was the major C20 PUFA, i.e. potential eicosanoid precursor in all phospholipids from fish fed MO, with the EPA level being twice that of AA in brain phosphatidylinositol (PI). DHGLA was the major C20 PUFA in all phospholipid classes from fish fed BO. In kidney and gill, EPA was the predominant C20 PUFA in all phospholipid classes, except PI, in fish fed MO. In kidney of fish fed BO, DHGLA was the major C20 PUFA in all phospholipid classes, except PE. In gill of fish fed BO, DHGLA was the major C20 PUFA in all phospholipid classes, including PI, where DHGLA was over 2.5-fold greater than AA. In homogenates of heart, kidney and gill from BO-fed fish the prostaglandin E1 (PGE1) concentration was significantly increased compared to MO-fed fish. In heart and kidney homogenates from fish fed MO the PGE3 concentration was significantly increased compared to fish fed BO. The ratio of PGE2/PGE1 was significantly reduced in brain, heart, kidney and gill homogenates from fish fed BO compared to those fed MO.